CRAC Channel Controls the Differentiation of Pathogenic B Cells in Lupus Nephritis - Li, Xue; Zeng, Qin; Wang, Shuyi; Li, Mengyuan; Chen, Xionghui; Huang, Yuefang; Chen, Binfeng; Zhou, Mianjing; Lai, Yimei; Guo, Chaohuan; Zhao, Siyuan; Zhang, Hui; et al. (Frontiers in Immunology, 2021)
Store-operated Ca2+ release-activated Ca2+ (CRAC) channel is the main Ca2+ influx pathway in lymphocytes and is essential for immune response. Lupus nephritis (LN) is an autoimmune disease characterized by the production of autoantibodies due to widespread loss of immune tolerance. In this study, RNA-seq analysis revealed that calcium transmembrane transport and calcium channel activity were enhanced in naïve B cells from patients with LN. The increased expression of ORAI1, ORAI2 and STIM2 in naïve B cells from patients with LN was confirmed by flow cytometry and western blot, implying a role of CRAC channel in B cell dysregulation in LN. For in vitro study, CRAC channel inhibition by YM-58483 or downregulation by ORAI1 specific siRNA decreased the phosphorylation of Ca2+/calmodulin-dependent protein kinase2 (CaMK2) and suppressed Blimp-1 expression in primary human B cells, resulting in decreased B cell differentiation and IgG production. B cells treated with CaMK2 specific siRNA showed defects in plasma cell differentiation and IgG production. For in vivo study, YM-58483 not only ameliorated the progression of LN, but also prevented the development of LN. MRL/lpr lupus mice treated with YM-58483 showed lower percentage of plasma cells in the spleen and reduced concentration of anti-double stranded DNA antibodies in the sera significantly. Importantly, mice treated with YM-58483 showed decreased immune deposition in the glomeruli and alleviated kidney damage, which was further confirmed in NZM2328 lupus mice. Collectively, CRAC channel controlled the differentiation of pathogenic B cells and promoted the progression of LN. This study provides insights into the pathogenic mechanisms of LN and that CRAC channel could serve as a potential therapeutic target for LN.